2008
DOI: 10.1126/science.1161621
|View full text |Cite
|
Sign up to set email alerts
|

Seeding and Propagation of Untransformed Mouse Mammary Cells in the Lung

Abstract: The acquisition of metastatic ability by tumor cells is considered a late event in the evolution of malignant tumors. We report that untransformed mouse mammary cells that have been engineered to express the inducible oncogenic transgenes MYC and Kras D12 , or polyoma middle T, and introduced into the systemic circulation of a mouse can bypass transformation at the primary site and develop into metastatic pulmonary lesions upon immediate or delayed oncogene induction. Therefore, previously untransformed mammar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
204
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(213 citation statements)
references
References 18 publications
8
204
0
1
Order By: Relevance
“…Recent studies suggest that inherited polymorphisms on 8q24 that powerfully modify solid tumor predisposition also influence MYC transcriptional regulation (30). Deregulation of the MYC oncoprotein confers a selective advantage on cancer cells in differing contexts by promoting proliferation, cell survival, differentiation blockade, epithelial to mesenchymal transition, and genetic instability, all of which can contribute to metastasis (27,(31)(32)(33). In fact, a recent report suggested that MYC functions as an indirect regulator of metastasis in a c-RAF-driven mouse model of non-small cell lung cancer by modulating growth, differentiation, and angiogenesis (34).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggest that inherited polymorphisms on 8q24 that powerfully modify solid tumor predisposition also influence MYC transcriptional regulation (30). Deregulation of the MYC oncoprotein confers a selective advantage on cancer cells in differing contexts by promoting proliferation, cell survival, differentiation blockade, epithelial to mesenchymal transition, and genetic instability, all of which can contribute to metastasis (27,(31)(32)(33). In fact, a recent report suggested that MYC functions as an indirect regulator of metastasis in a c-RAF-driven mouse model of non-small cell lung cancer by modulating growth, differentiation, and angiogenesis (34).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, a latent niche mechanism may act in conjunction with these mechanisms, other tumor-cell-autonomous mechanisms, or both to promote inappropriate self-renewal of neighboring cells. For example, Podsypanina et al recently demonstrated that under experimental conditions normal mammary cells can persist in the lung for extended periods and subsequently become foci for new tumor growth when they are transformed (36). It is conceivable that they are maintained by a latent niche mechanism and that self-renewal or survival signals could predispose such cells to progress to tumors after the acquisition of subsequent transforming mutations (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…27 Even in RAGnull mice, normal breast cells can be recruited to the lungs without oncogene activation. 28 Experimental activation of oncogenes after homing results in metastatic colonization. This finding suggests that tumor cells may travel to potential metastatic sites at any stage of the multistep malignant transformation sequence.…”
Section: Acquisition Of Metastatic Potential In Primary Tumorsmentioning
confidence: 99%